2023
DOI: 10.5802/crgeos.159
|View full text |Cite
|
Sign up to set email alerts
|

Volcanism and tectonics unveiled in the Comoros Archipelago between Africa and Madagascar

Abstract: Volcanism and tectonics unveiled in the Comoros Archipelago between Africa and Madagascar Volcanisme et tectonique découverts le long de l'archipel desComores entre l'Afrique et Madagascar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…Different loading masses corresponding to various volumes of volcanic rock involved in volcanic edifice building were simulated in models of several volcanic edifices 200 m tall and with diameters of 3.5 km as suggested by bathymetric data [48,49,82], corresponding to a conical volume of 0.6 km 3 and a mass of 1.8 × 10 12 kg. This study discusses the loading mass that explains the observed subsidence.…”
Section: Volcanic Edifice Loading and Isostatic Adjustmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Different loading masses corresponding to various volumes of volcanic rock involved in volcanic edifice building were simulated in models of several volcanic edifices 200 m tall and with diameters of 3.5 km as suggested by bathymetric data [48,49,82], corresponding to a conical volume of 0.6 km 3 and a mass of 1.8 × 10 12 kg. This study discusses the loading mass that explains the observed subsidence.…”
Section: Volcanic Edifice Loading and Isostatic Adjustmentmentioning
confidence: 99%
“…New volcanic edifices have been built in the last few thousand years during the sea level rise, including relatively young volcanic features east of Mayotte [1,33,48,49], along the slope of the main structure and volcanic rocks ranging in age from 2.2 to 7.965 kyr [56][57][58]. To our knowledge, there are no published ages for submarine edifices on the Mayotte slope.…”
Section: Vertical Movements and Isostatic Adjustmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a) has regained attention from the scientific community since 2018 due to the birth of a fast-building submarine volcanic edifice, 50km east of Mayotte, Fani Maoré volcano (Lemoine et al, 2020;Feuillet et al, 2021;Berthod et al, 2021a). Marine geophysical surveys have since revealed that the archipelago is only the emerged portion of a much wider province of volcanic ridges and seamounts extending north and east of the islands (Tzevahirtzian et al, 2021;Thinon et al, 2022). The origin of volcanism in the Comoros archipelago remains enigmatic in many aspects since none of the proposed interpretations can explain all the observations.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these advances are direct outcomes from the ANR COYOTES project (https://anr.fr/Projet-ANR-19-CE31-0018), from oceanic cruises such as SIS-MAORE (doi:10.17600/18001331), and from the now regular MAYOBS surveys (doi:10.18142/291). In Thinon et al [2022] for instance, extension of the submarine volcanism in the northern Mozambique channel is evidenced, and the regional geodynamics is investigated by means of marine geophysics. This first part also questions the nature of the lithosphere beneath the Comoros archipelago, by probing its thermal state from literature and newly published heat flow measurements [Rolandone et al, 2022] and its structure from teleseismic receiver functions [Dofal et al, 2022].…”
mentioning
confidence: 99%